Increasing the sustainability of alkali-activated binders: The use of sugar cane straw ash (SCSA) - Moraes, J. C.B. [UNESP]; Tashima, M. M. [UNESP]; Akasaki, J. L. [UNESP]; Melges, J. L.P. [UNESP]; Monzó, J.; Borrachero, M. V.; Soriano, L.; Payá, J. (Elsevier, 2016)
Alkali-activated binders are the new trend in building construction studies due their good mechanical properties and environmental advantages. These type of binders are obtained by a mixing of a solid precursor with an activating solution. In this study, the influence of sugar cane straw ash (SCSA) obtained from an auto-combustion process on blast-furnace slag (BFS) based alkali-activated binders was assessed as solid precursor. The studied proportions of BFS/SCSA were 100/0 (control), 85/15, 75/25, 67/33 and 50/50 (by mass). Regarding to the activating solutions, three different mixtures were used: only NaOH (8 mol kg−1 Na+) and two different combinations of NaOH with sodium silicate (8 mol kg−1 Na+ and SiO2/Na2O molar ratios of 0.50 and 0.75). The water/binder was maintained constant. To assess the influence of SCSA on BFS-alkali activated binders, mortars were evaluated in terms of compressive strength (3–90 days curing time at room temperature and 3 days at 65 °C); and pastes were studied to justify these results by means of thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR) and field emission scanning electron microscopy (FESEM). The presence of SCSA in the binder greatly improved the compressive strength when compared to the control BFS mortars, reaching values higher than 50 MPa after 90 days. SCSA/BFS samples activated with sodium hydroxide yielded similar compressive strength values to those obtained for BFS mortars activated with sodium silicate. In the new binders, the partial replacement of BFS, the total replacement of sodium silicate solution and a new way of valorizing sugar cane straw enhanced sustainability.
Keywords: Biomass; Mechanical properties; Microstructural characterization; Renewable resources; Silicates